Antitubercular drug discovery: the molecular modification as promise tool - Dutra, Luiz Antonio [UNESP]; Melo, Thais Regina Ferreira de [UNESP]; Chin, Chung Man [UNESP]; Santos, Jean Leandro [UNESP] (My University, 2012)
Tuberculosis is a chronic infectious disease caused by etiologic agent Mycobacterium tuberculosis. "It has been reported that rates of incidence is increasing and each year around 8.9-9.9 million new cases are detected”. The current TB therapy presents several problems such as long-term therapy, drug resistance, no-compliance to therapy and few therapeutic sources to treat the disease. The discovery of new drugs safer and more efficient is urgent. The molecular modification is an important tool that allows discovering new compounds that can be win these challenges. In this work, we summarize the main strategies useful to obtain a new antitubercular drug.
Keywords: Tuberculosis; Antitubercular drugs; New drugs; Molecular modification